The mediating role of perceived behavioral control in the relationship between entrepreneurship education and entrepreneurial intentions of university students in Ethiopia - Messele Kumilachew Aga (Journal of Innovation and Entrepreneurship, 2023)
Unemployment of graduates from higher education institutions has become a common phenomenon in Ethiopia. To minimize this problem, entrepreneurship development and promoting entrepreneurial ecosystems have been considered as a remedy. Among others, this could be achieved through fostering entrepreneurship education. Hence, the purpose of this paper is to investigate the mediating role of perceived behavioral control in the relationship between entrepreneurship education and entrepreneurial intentions in Ethiopian Universities. Explanatory research design was used and data were collected using a self-administered questionnaire from a sample of 335 undergraduate students who have taken the course entrepreneurship in four Ethiopian universities. Structural Equation Modeling (SEM) approach using AMOS software was employed and confirmed both measurement and structural model fit before analysis. Then, the findings revealed that entrepreneurship education has a positive and significant effect on entrepreneurial intentions and perceived behavioral control. Moreover, perceived behavioral control positively predicts entrepreneurial intentions. The findings further explained that perceived behavioral control has a partial mediating effect in the relationship between entrepreneurship education and entrepreneurial intentions. Therefore, universities in Ethiopia should work on different initiatives that enhance knowledge, attitude, and skills of students on entrepreneurship that could help them to develop perceived behavioral control so as to enhance their intentions to become nascent entrepreneur after their graduation.
Keywords: 650; Ethiopia; Perceived behavioral control; Entrepreneurship education; Entrepreneurial intentions; University students